Food loss in a hungry world, a problem? (2014)
Mainly in developing countries, food loss and waste is a problem that is difficult to measure. Investigations have been conducted in industrialized countries; however, consistent evidence of how much is really being depleted is limited. The accessible data give the illusion of evidence, but are supported by very restricted facts. In recent years, food waste and loss have gained importance because more than 35% of food is wasted. Nevertheless, with this percentage of food, most of the 800 million people that go hungry every day in the world could be fed. This reflection paper aims to describe the different approaches and meanings of food waste, food loss and food wastage. Similarly, this article identifies the phases of the food supply chain where food is being lost and wasted. Based on the available data, developed and developing countries are compared. It was concluded that, in developed countries, the most important losses are in the consumption phase; in developing countries, the losses take place in the growing and harvesting phase. Changing consumption habits as well as the improvement of cropping and harvesting processes could be an option for reducing this problem, especially in developing countries.